Inelastic response prediction of CFST columns and connections subjected to lateral loading. (May 2017) - Zhu, Haiqing; Stephens, Max T.; Roeder, Charles W.; Lehman, Dawn E.
Abstract: Concrete filled steel tubes (CFST) are composite structural elements which provide an economical and efficient alternative to conventional reinforced concrete and structural steel construction. Under seismic loading, CFSTs undergo reversed cyclic loading, and robust connections capable of sustaining cyclic lateral load demands, while minimizing damage and degradation, are required. Previous research has utilized numerical and experimental methods to demonstrate the performance of an embedded ring (ER) CFST column-to-cap beam/foundation connection in which an annular ring is welded to the end of the steel tube, and embedded in the cap beam/foundation concrete. However, due to the complexities associated with modeling the non-linear cyclic behavior of the ER connection (including the cyclic behavior of the concrete fill and the composite interaction of the materials), prior numerical efforts have focused primarily on monotonic behavior and failure envelopes rather than cyclic behavior. This deficiency is addressed here. A detailed continuum model capable of capturing the non-linear cyclic behavior of the ER connection is introduced and validated using experimental data. The proposed model is shown to predict damage and behavior of the ER connection subjected to reversed-cyclic loading with a reasonable accuracy; failure modes, hysteretic curves, resistance at target drifts, and drifts and steel strains at the initiation of steel tearing compare well with experimental observations. Highlights: An economical and efficient embedded CFST column-to beam connection was introduced. The ductile damage criteria were applied in the FEA models to simulate the steel tube tearing phenomenon. A pre-cracking contacting method was developed to handle the infill concrete cracking open and closure. The 3-D FEA models were verified by the cyclic loading test results including damage patterns, hysteretic curves, and local strains.